2020
DOI: 10.1039/c9nj05956c
|View full text |Cite
|
Sign up to set email alerts
|

A boron-doped carbon aerogel-supported Cu catalyst for the selective hydrogenation of dimethyl oxalate

Abstract: The modification of B in carbon support can modulate the hydrogenation selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…On the whole, the total acidic amount of boron‐containing LaCoO 3 is 2–4 fold that of pristine LaCoO 3 . Specifically, boron acts as electron acceptor for Lewis acids, and metal ions also have a strong ability to obtain electrons [39] . Strong acidity is helpful for the adsorption of C 3 H 8 and activation of C−H bond [40]…”
Section: Resultsmentioning
confidence: 99%
“…On the whole, the total acidic amount of boron‐containing LaCoO 3 is 2–4 fold that of pristine LaCoO 3 . Specifically, boron acts as electron acceptor for Lewis acids, and metal ions also have a strong ability to obtain electrons [39] . Strong acidity is helpful for the adsorption of C 3 H 8 and activation of C−H bond [40]…”
Section: Resultsmentioning
confidence: 99%
“…Metal-N species [27,30,40,[44][45][46][47]128] Regulate acid site [28] Change reduction state [35,42] Improve hydrophilicity [28] Increase alkalinity of site [12,23,27,34,45,130] Interaction between metal and N [26,30] Increase the adsorption of substrate [33] Improve metal dispersion [24,25,27,29,31,32,35,36,40,44,45,48] Pyrolysis Similar to N, S doping, B atoms can also be easily incorporated into the carbon skeleton due to its comparable atomic size with carbon. [57,[62][63][64][65][66][67][68] The role of B is basically to form a strong interaction with the metal, thus affecting the electronic and geometric state of the metal (Table 2). [57,62,[63][64][65]…”
Section: Metal Catalysts Anchored By S B and Pmentioning
confidence: 99%
“…Adjust the S-containing precursor Change calcination temperature B Improve metal dispersion and stability [57,[62][63][64][65][66][67][68]73] Regulate electronic structure of metal [63,65,67,71] Regulate acid site [64,65] Regulate the adsorption/desorption strength of substrate/ intermediate [57,62,65] Change reduction state [64,65,67] Pyrolysis of B-containing precursor Chemical vapor deposition Adjust the P-containing precursor Change processing time Change calcination temperature P Metal-P species [70,72] Regulate acid site [50] Improve metal dispersion and stability [57,61,72,75] Regulate the affinity between carbon matrix and metal precursors [61] Regulate electronic structure of metal [71] Regulate the adsorption/desorption strength of substrate/ intermediate [60,76] Pyrolysis of P-containing precursor Phosphoric acid pretreatment Adjust the P-containing precursor Change calcination temperature (Table 3) are of significance in a diverse range of applications, which is worthy of more efforts and breakthroughs.…”
mentioning
confidence: 99%
“…Moreover, due to its less valence electrons than carbon, hetero boron atom can play the part of electron acceptor, which can effectively adjust acid-base distribution on catalyst surface. [31] Chen [32] et al demonstrated that doping boron would enhance the electron transfer from support to the gold clusters, thus improved the catalyst activity. Chen [33] et al concluded that the strengthened interaction between copper and CA originated from boron doping improved the ratio of Cu + /(Cu + + Cu 0 ), further enhancing EtOH selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Boron is considered as an ideal dopant due to its similar atomic radius as carbon. Moreover, due to its less valence electrons than carbon, hetero boron atom can play the part of electron acceptor, which can effectively adjust acid‐base distribution on catalyst surface . Chen et al.…”
Section: Introductionmentioning
confidence: 99%